Building Information Modeling and Internet of Things integration for smart and sustainable environments: A review. (20th August 2021) - Malagnino, Ada; Montanaro, Teodoro; Lazoi, Mariangela; Sergi, Ilaria; Corallo, Angelo; Patrono, Luigi
Abstract: During the last decades, society has increasingly moved towards the adoption of digital solutions in almost every aspect of people's lives with the aim of enhancing daily activities. At the same time, the environmental impact of the built environment has attracted the attention of public opinion that is gradually perceiving the necessity of limiting its negative effects in order to safeguard the Earth and people's wellbeing. The Internet of Things is one of the biggest ecosystems that is bringing innovations encompassing digital solutions in almost every sector. On the other hand, the Building Information Modeling approach allows for data sharing among stakeholders, traceability, and the integrated management of the building or infrastructure life-cycle through a 3D informative virtual model. Our study reviews existing research works and technological solutions that integrate these two important topics to enhance the sustainability of the built environment, making it smarter. The presented review analyses the existing papers available in literature from January 2015 to December 2020, to present the best practices in this integration and discuss limitations of the identified solutions. Based on the outcomes of the analysis and aiming at the creation of a solid knowledge basis for the community interested in the sector, a comprehensive modular architecture has been proposed. Finally, new directions for future works are presented by discussing how the proposed architecture can actually facilitate the design and development phases.